2006
DOI: 10.1097/01.aog.0000195824.51919.81
|View full text |Cite
|
Sign up to set email alerts
|

Fas (TNFRSF6) Gene Polymorphism in Pregnant Women With Hemolysis, Elevated Liver Enzymes, and Low Platelets and in Their Neonates

Abstract: II-2.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 27 publications
1
10
0
Order By: Relevance
“…The mechanisms are very complicated. Gene variants in the Fas receptor, the VEGF gene, and the coagulation factor V Leiden mutation are associated with increased risk of the HELLP syndrome compared to healthy women [51, 69, 77]. Variants in the Bell polymorphism [93] and the TLR-4 increased the risk of HELLP significantly more than the risk of preeclampsia [52].…”
Section: Discussion and Future Directionsmentioning
confidence: 99%
See 3 more Smart Citations
“…The mechanisms are very complicated. Gene variants in the Fas receptor, the VEGF gene, and the coagulation factor V Leiden mutation are associated with increased risk of the HELLP syndrome compared to healthy women [51, 69, 77]. Variants in the Bell polymorphism [93] and the TLR-4 increased the risk of HELLP significantly more than the risk of preeclampsia [52].…”
Section: Discussion and Future Directionsmentioning
confidence: 99%
“…Sziller et al reported that a single adenine (A) to guanine (G) polymorphism at position −670 in the Fas receptor ( TNFRSF6) results in decreased Fas synthesis. A study by Sziller et al comprised women with a HELLP syndrome ( n = 84) and normotensive women ( n = 83) [51]. Cells from the buccal mucosa were obtained by rotating cotton swab within 1 hour after delivery.…”
Section: Polymorphism Of the Fas Receptormentioning
confidence: 99%
See 2 more Smart Citations
“…A variety of other perinatal outcomes, such as small for gestational age or intrauterine growth restriction (Svensson, Pawitan, Cnattingius, Reilly, & Lichtenstein, 2006), pre‐eclampsia (Sziller et al, 2005), and HELLP syndrome (hemolytic anemia, elevated liver function tests, and low platelets; Sziller et al, 2006) are beginning to be studied as to their genetic basis, thus the trend toward a genomic approach is growing. Research is also showing the relationships among genomic, proteomic, and metabalomic predictors and environmental interactions that may place some women at greater risk of adverse pregnancy outcomes than others.…”
Section: Introductionmentioning
confidence: 99%